2015
DOI: 10.3329/bjz.v43i1.26143
|View full text |Cite
|
Sign up to set email alerts
|

Status of ganges dolphin, Platanista gangetica gangetica (Roxburgh, 1801) in the river Buriganga, Dhaka

Abstract: Population abundance and density of the Ganges River Dolphin Platanista gangetica gangetica (Roxburgh, 1801) was studied in the Buriganga River from December 2012 to November 2013.The survey was conducted twice a month. The dolphins were counted directly and applied in transect length of 10.5 km within 15 km stretches of the river. A total of 34 sightings of dolphins were recorded both in individuals and groups. We encountered the dolphins at the rate of 0.48 dolphins per km in the Buriganga River. Highest bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Boats maintained a constant speed range of 7-10 km/h. Survey design followed previous studies conducted by different authors [15,[25][26][27][28][29][30][31]. The observation team mostly consisted of three researchers.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Boats maintained a constant speed range of 7-10 km/h. Survey design followed previous studies conducted by different authors [15,[25][26][27][28][29][30][31]. The observation team mostly consisted of three researchers.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Baki (2017) recorded 62 sightings in the Turag River from 2012-2023. In addition, two studies reported 29 and 34 sightings in 2003-2004 and 2012-2023 from the river Buriganga, respectively (Alam et al 2015, Alam & Sarker 2012. A single specimen was recorded from a marsh called Chanda Bill at Gopalganj in 2010.…”
mentioning
confidence: 99%